Woman as subject/object: A critique of feminist writings on prostitution and pornography. - Bruckert, Chris. (University of Ottawa (Canada), 1991)
The construction of woman as object/other in the dominant discourse is an accepted problematic in feminist scholarship. This is understood to be a function of the androcentric nature of the academic, linguistic and social spheres that mediate our understanding/experience. In this context, reality is dichotomized, and woman is the object/other against which man identifies himself as subject. This consciousness poses a fundamental epistemological challenge to feminist scholars: how to construct woman as the subject of discourse and overcome woman's deeply rooted social definition and consciousness of object/other. The positions and understandings of contemporary feminist theory on how to actualize this understanding in praxis are reviewed and a typology considered that assesses feminist thought in relation the conceptualization of woman and strategies to construct woman as the subject in discourse. A sample of feminist writings on prostitution and pornography are analyzed to determine if the ideological and epistemological assumptions of the dominant discourse, rejected in feminist theory, are reproduced in substantive applications of feminism. It is argued that in much of the feminist prostitution and pornography literature reviewed, skin and sex trade workers are denied legitimacy and voice; they are the deconstructed subject who is symbol/victim/object. Further there is a failure to transcend the conceptual boundaries of androcentric thought and therefore the dominant constructs are implicitly legitimated. It is concluded that some of the current applications of feminist theory contravenes the established political/personal mandate of feminism to redefine woman as the subject of discourse. It is suggested that a feminist framework is required that is conscious of itself, its own ideology, socially imposed parameters and its relation to the dominant discourse against which it defines itself.
Keywords: Literature, Modern.